Gladys the magic chicken [book with audioplayer] - Rubin, Adam, 1983- ([Library Ideas, LLC], 2023)
In Ancient Times, Gladys the dancing chicken goes on an epic adventure when she is mistaken for a magical chicken who grants wishes to those she encounters.